Penerapan Hukuman Mati Bagi Pelaku ‎Tindak Pidana Korupsi - muwahid muwahid (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: Research on the application of the death penalty ‎for perpetrators of corruption is a research library , with the ‎purpose to find out: first, setting the death penalty in law of ‎corruption; secondly, the application of the death penalty for ‎perpetrators of corruption in a human rights perspective. ‎Primary data were obtained from the legislation, secondary ‎data obtained from the criminal law books, law journals, and ‎legal dictionaries. Data was collected to study the document. ‎While the use of data analysis techniques